1998
DOI: 10.1098/rspb.1998.0472
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of a recombinant protein of Trichuris trichiura

Abstract: The pore-forming protein of the human whipworm, Trichuris trichiura, has been postulated to facilitate invasion of the host gut and enable the parasite to maintain its syncytial environment. The data presented here describe the first, to our knowledge, molecular characterization of a pore-forming protein in any helminth and provide a unique demonstration of the functional interaction between a parasite antigen and host molecules. Immunological screening of a T. trichiura cDNA library with T. trichiura infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Drake et al . characterized a pore-forming protein that T. muris [14] and T. trichiura [13] use to drill holes in the host cell membrane. Furthermore, it has been suggested that a thioredoxin-like protein secreted by the pig whipworm Trichuris suis plays a role in mucosal homeostasis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Drake et al . characterized a pore-forming protein that T. muris [14] and T. trichiura [13] use to drill holes in the host cell membrane. Furthermore, it has been suggested that a thioredoxin-like protein secreted by the pig whipworm Trichuris suis plays a role in mucosal homeostasis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this progress, and the tractability of the T. muris model, very few proteomic studies have been conducted, and only a handful of reports have described proteins secreted by Trichuris spp. [9, 10, 11, 12, 13, 14]. Drake et al characterised a pore-forming protein that T. muris [14] and T. trichiura [13] use to drill holes in the host cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…[9, 10, 11, 12, 13, 14]. Drake et al characterised a pore-forming protein that T. muris [14] and T. trichiura [13] use to drill holes in the host cell membrane. Furthermore, it has been suggested that a thioredoxin-like protein secreted by the pig whipworm Trichuris suis plays a role in mucosal homeostasis [11].…”
Section: Introductionmentioning
confidence: 99%
“…The Tm -WAP gene shares high sequence alignment with the T . trichiura putative porin proteins, TT95 [ 24 ] and TT52 [ 25 ], at 54% and 47% amino acid sequence identity, respectively ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…muris ES are cross-reactive to anti- Tm -WAP49 and anti- Tm -WAP-F8+ Na -GST-1 sera by western blot. Furthermore, Tt 52 and Tt 95 have been described for their ability to generate pores in a planar lipid bilayer [ 12 , 24 , 25 ]. Future studies testing the ability of Tm -WAP antisera to inhibit pore-formation, preventing stichosome penetration and maintenance in the colonic mucosa would be important to fully realize the vaccine potential of WAP.…”
Section: Discussionmentioning
confidence: 99%